Information needs, access and coping strategies for cervical cancer clients at Mulago Uganda Cancer Institute. - Kagimu, Rogers (Journal of Health Informatics in Africa, 2019)
Background The advent of effective infection control and treatment measures has shifted the burden of disease from infectious causes to chronic; non-communicable diseases (NCDs). Diseases such as cardiovascular and cancer are on the rise globally with a rapidly growing crisis in low-income and middle-income countries (LMICs). In 2015 for example, cancer was responsible for 8.8 million deaths globally and approximately 70% of these deaths occurred in LMICs. With lung, female breast, stomach and colorectal cancers combined with liver and cervical cancer (CaCx) explaining over half the incidence burden (54%) in LMICs. For CaCx, the pattern is striking since around 85% of women diagnosed and 87% of those who die from the disease live in LMICs. In Africa, CaCx is high in the sub-Saharan region with Uganda being ranked 10th with 44.4|100,000 women; Age-standardized incidence rate of CaCx cases. Among the contributing factors for the high incidence of the disease in the country include; lack of screening tests and vaccines to prevent HPV limited access to cervical screening programs as well as lack of information among others. This study investigated the information needs priorities about CaCx and coping information access strategies for CaCx clients and the general public. Material The study was conducted at Uganda Cancer Institute (UCI) gynae-clinic and participants were women with CaCx (CaCx clients), women without CaCx (general public) and healthcare professionals in active care for CaCx (gynae oncologists, nurses, & clinical officers). All participants were first informed of the study and those willing to take part, were recruited between April and May, 2018. For eligibility, participants had to be adults of above 18 years, able to speak the local language (Luganda) or English or both, confirmed evidence of CaCx or CaCx negative. Clients who were attending the clinic for the first time, and unaware of their diagnoses were excluded. While recruiting CaCx clients, a list was generated and participants randomly selected. For healthcare professionals and women without CaCx, convenient sampling and simple random sampling were used. Interviews were audio recorded and hand written notes were done throughout the interview session. Focus Group Discussions (FGDs) comprised of participants with and without CaCx. Key informant interviews (KIIs); nurses (n=2) clinical officers (n=2) and gynae-oncologists (n=2), and In-depth individual interviews (IDIs) comprised of women without CaCx (n=4). Data collected was transferred from the recorders onto a secured password protected computer. Notes taken during interviews together with consent documents were securely kept under lock and key for further reference. Interviews were transcribed then verbatim transcriptions were generated. Analysis of data was done using Atlas.ti version7 taking an exploratory approach (inductive content analysis), and findings presented as themes. Research and Ethics Committees of Makerere University, and Uganda Cancer Institute (UCI-REC) approved this study, and participants consented to take part. Each participant consented before taking part in the study. Results It was evident that clients desire more extensive information concerning the disease, treatment, and prognosis. Important information themes are highlighted in bold italics. CaCx Symptoms CaCx noted that if information on symptoms was known to them and to the general public, there is/was a high likelihood to seek medical attention when the disease has not reached advanced stages. Screening Participants needed screening information on where to find this service, how it is done and who to seek for it and when. Such information will help in early diagnosis; a point when medical intervention can still make a long-term difference. Dos and Don’ts Information concerning health-lifestyle which contributes to improved health was among what needed to be shared to CaCx clients as supported hereunder. Treatment Side Effects CaCx clients want to know information concerning the side effects of the different kinds of treatment lines they receive along their care journey. They noted that along treatment, both short and long-term side effects occur; something they need to be cognizant of since some effects turn out to lead to a deteriorating health. CaCx and its Causes. Many people seem not aware of this silent killer as it emerged that basic information relating to CaCx such as what it is, where it affects, who is at risk and the risk factors among others were not obviously known to them and needed to be shared to the public. The commonest mode of information sharing is by the word of mouth (face-face) and this does not facilitate adequate information sharing since it is affected by language barrier besides the clinic being a high-volume facility with small numbers of care providers. Conclusion Information needs slightly differed between CaCx clients and those of the general public yet between CaCx clients and healthcare professionals, they were comparable. Majority CaCx clients prefer to receive extensive information at their first diagnosis. Information about treatment, procedures as well as side effects, and prognosis are of particular relevance. Findings demonstrated that information seeking continues from diagnosis to follow-up. Therefore, healthcare providers listening to the clients might be more effective way to prevent and fight CaCx. It is also imperative to make use of the increasing adoption of ICTs to develop a centralized information portal on CaCx where all awareness information can easily be accessed by whoever might need it. Then efforts be made by referring and encouraging clients to use this portal as an effective way to further increase CaCx awareness. Keywords; Cervical cancer, information access, information needs.